Historical Analysis of Nepal’s International Relations from a Defence Perspective - Thapa, Rabi Raj (NCWA Annual Journal, 2024)
Nepal has a track record of being one of the oldest as well as ever sovereign and independent nations of the world. Today, Nepal’s international relations is going through a critical and vulnerable phase. One of the main reasons for this may be that Nepal abruptly abandoned and stopped learning from the deeds of the founding heroes and has not been able to chart and steer an effective national policy strategy in its international relations. In the past, many of the rulers used to be kings and military generals and they had adopted hard power as their main instruments. Today, Nepal cannot think of hard power but rather soft power and smart power. At this point, it would be pertinent to reflect on Nepal’s past international relations policy strategy so it may help to understand the value and role of national security policy strategy as an integral part of successful international relations in the future. This paper has tried to examine the international relations of contemporary Nepal from a defense perspective based on historical references.